2020
DOI: 10.1186/s13104-020-04956-z
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9-mediated labelling of the C-terminus of human laminin β1 leads to secretion inhibition

Abstract: Objectives: The laminins (LM) are a family of basement membranes glycoproteins with essential roles in supporting epithelia, endothelia, nerves and muscle adhesion, and in regulating a range of processes including cell migration, stem cell maintenance and differentiation. However, surprisingly little is known about the mechanisms of turnover and remodelling of LM networks due to lack of appropriate tools to study these processes at the necessary resolution. Recently, the nematode C. elegans ortholog of human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Although genetic tagging of BM-specific proteins has been achieved in Drosophila and Caenorhabditis elegans [7] , [11] , [12] , [13] , genetic modification of BM-specific proteins in mammalian cells often disturbs their expression, function, or both [29] , [30] . Shaw et al reported that genetic tagging of the laminin β1 subunit on its C-terminus with a photoconvertible fluorescent protein prevented the subunit from being secreted from the human lung carcinoma cell line A549, even though it was translated in the cells [31] . We also attempted to tag the laminin α5 subunit with EGFP at the N-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic tagging of BM-specific proteins has been achieved in Drosophila and Caenorhabditis elegans [7] , [11] , [12] , [13] , genetic modification of BM-specific proteins in mammalian cells often disturbs their expression, function, or both [29] , [30] . Shaw et al reported that genetic tagging of the laminin β1 subunit on its C-terminus with a photoconvertible fluorescent protein prevented the subunit from being secreted from the human lung carcinoma cell line A549, even though it was translated in the cells [31] . We also attempted to tag the laminin α5 subunit with EGFP at the N-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…However, until recently, the key bottleneck in our understanding of mammalian, and indeed vertebrate BMs, has been the lack of models in which endogenous BM components are labelled. Several attempts to generate such models have been unsuccessful (Shaw et al, 2020), and in vivo studies have relied upon knock-in reporters which do not necessarily reflect endogenous protein expression and can be expressed ectopically and/or interfere with native protein function (Yamaguchi et al, 2022, Sztal et al, 2011, Futaki et al, 2023). The recent success by Morgner et al (2023) in generating a Lamb1-Dendra2 mouse model provided proof-of-principle that fluorescently tagging BM components in mouse is feasible, and in this study, we have advanced one step further by generating a mouse line in which the BM ubiquitous COL4A1 is labelled.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the absence of homozygous animals is that heterotrimers containing two mTurq2-COL4A1 molecules (collagen α1/α1/α2 (IV)) may cause problems with secretion; mutant COL4A1 or COL4A2 has been shown to accumulate within cells, reducing secretion and leading to extracellular deficiency (Jeanne et al, 2015). Inhibited secretion was also observed with C-terminal tagged human laminin β-1 in adenocarcinoma cells (Shaw et al, 2020). Alternatively, given that the 7S domain is important for crosslinking collagen IV into a lattice network, it may be that two mTurq2 molecules per collagen IV trimer interferes with 7S-mediated crosslinking, but one mTurq2 per trimer can be tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans, mNeonGreen was inserted at the N-terminus of the collagen IV α2/let-2 gene, resulting in viable heterozygotes but nonviable homozygotes 14 . There was an attempt to adapt the Dendra2 tagging of laminin b1 used in C. elegans 53 to mammalian cells, but secretion failed 19 . More recently, a knock-in mouse model that expresses endogenously tagged laminin b1-Dendra2 fusion protein has been developed and used to identify BM-producing origins and dynamics in breast tumours 21 .…”
Section: The Challenges and Importance Of Fluorescence Tagging Of End...mentioning
confidence: 99%
“…These properties include 1) large modular structures, 2) specialized intracellular transport and secretory mechanisms, 3) post-translational processing, 4) the assembly of supramolecular complexes, 5) complex molecular interactions and 6) unique extracellular physicochemical environments, such as redox status. While a few individuals of C. elegans and Drosophila have been manipulated to express fluorescently tagged endogenous BM proteins with normal functions 14,18 , mice expressing fluorescent tag-fused core BM proteins have exhibited functional abnormalities [19][20][21] . Therefore, generating mice that express endogenous core BM proteins fused with a fluorescent tag while maintaining normal function remains a major challenge.…”
Section: Introductionmentioning
confidence: 99%